Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
when you add ln, you multiply
ln((5x-1)(x-6)=ln6 do now FOIL
ln(5x^2-30x-x+6)=ln6
therefore
5x^2-31x+6=6 and
5x^2-31x=0 furthermore
x(5x-31)=0
one solution is 0, which we will reject
the other solution is 5x=31
x=31/5
ln((5x-1)(x-6)=ln6 do now FOIL
ln(5x^2-30x-x+6)=ln6
therefore
5x^2-31x+6=6 and
5x^2-31x=0 furthermore
x(5x-31)=0
one solution is 0, which we will reject
the other solution is 5x=31
x=31/5
ln(5x - 1) + ln(x - 6) = ln(6)
ln((5x - 1)(x - 6)) = ln(6)
ln(5x(x - 6) - 1(x - 6) = ln(6)
ln(5x(x) - 5x(6) - 1(x) - 1(-6)) = ln(6)
ln(5x² - 30x - x + 6) = lm(6)
ln(5x² - 31x + 6) = ln(6)
5x² - 31x + 6 = 6
5x² - 31x + 6 - 6 = 6 - 6
5x² - 31x + 0 = 0
x = -(-31) +/- √((-31)² - 4(5)(0))
2(5)
x = 31 +/- √(961 - 0)
10
x = 31 +/- √(961)
10
x = 31 +/- 31
10
x = 31 + 31 x = 31 - 31
10 10
x = 62 x = 0
10 10
x = 6²/₅ x = 0
ln((5x - 1)(x - 6)) = ln(6)
ln(5x(x - 6) - 1(x - 6) = ln(6)
ln(5x(x) - 5x(6) - 1(x) - 1(-6)) = ln(6)
ln(5x² - 30x - x + 6) = lm(6)
ln(5x² - 31x + 6) = ln(6)
5x² - 31x + 6 = 6
5x² - 31x + 6 - 6 = 6 - 6
5x² - 31x + 0 = 0
x = -(-31) +/- √((-31)² - 4(5)(0))
2(5)
x = 31 +/- √(961 - 0)
10
x = 31 +/- √(961)
10
x = 31 +/- 31
10
x = 31 + 31 x = 31 - 31
10 10
x = 62 x = 0
10 10
x = 6²/₅ x = 0
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.